Preliminary Results on the Use of Leather Chrome Shavings for Air Passive Sampling - D. Sanjuán-Herráez; L. Chabaane; S. Tahiri; A. Pastor; M. de la Guardia (Journal of Analytical Methods in Chemistry)
A new passive sampler based on low-density polyethylene (LDPE) layflat tube filled with chrome shavings from tannery waste residues was evaluated to determine volatile organic compounds (VOCs) in indoor and outdoor areas. VOCs were directly determined by head space-gas chromatography-mass spectrometry (HS-GC-MS) without any pretreatment of the sampler and avoiding the use of solvents. Limit of detection values ranging from 20 to 75 ng sampler−1 and good repeatability values were obtained for VOCs under study with relative standard deviation values from 2.8 to 9.6% except for carbon disulfide for which it was 22.5%. The effect of the amount of chrome shavings per sampler was studied and results were compared with those obtained using empty LDPE tubes, to demonstrate the capacity of chrome shavings to adsorb VOCs.